A micromolar concentration of lipo-chitooligosaccharide (Nod Bj V [C18:1, MeFuc]) regulates the emergence and seed productivity of rapid cycling canola (Brassica napus [L.]) plants. (1st November 2016) - Schwinghamer, Timothy; Souleimanov, Alfred; Dutilleul, Pierre; Smith, Donald L.
ABSTRACT: The objective of this experiment was to assess whether or not the application of lipo-chitooligosaccharide (Nod Bj V [C18:1, MeFuc]) (LCO) would increase yield factors under conditions that would inhibit canola ( Brassica napus L.) productivity. The seed application reduced the percentage of plants that were unproductive by 15.10% compared to plants grown from untreated seeds. Based on the 95% confidence interval for the difference, untreated plants would produce 38 to 3% fewer seeds than plants grown from LCO treated seeds. The experimental conditions were artificial, but further experimentation, with agricultural cultivars grown in greenhouses where natural conditions were simulated, confirmed that LCO treatment can contribute to canola yield.